Analysis of regional differences in the influence of China’s urbanization modes on rural sustainable development - Huang, Dongmei; Zheng, Qingchang (Frontiers in Environmental Science, 2022)
During the process of rapid urbanization in China, rural development has become increasingly dependent on cities. Policies to promote rural development emphasize the formation of an urbanization mode for the coordinated development of large, medium, and small cities as the driving force for rural development, but the policies do not define the regional interurban scale structure relationship. This study uses provincial panel data of China from 2004-2017 and analyzes the effect of provincial spatial structure on rural sustainable development in different regions through the dynamic system generalized method of moments. The results show (1) that China's spatial structure has significant regional differences: It is flat the eastern region and more concentrated in the central and western regions. (2) China's rural sustainable development efficiency has been declining, and in the central region it is higher than in the east and west regions. (3) At present, the provincial urbanization modes in different regions of China mainly stimulate rural sustainable development through three factors, i.e., urban population scale, industrial structure, and foreign direct investment. This study will help optimize the provincial spatial structure according to local conditions and promote rural sustainable development and regional balance.